A Follow-Up Investigation of Mental Health Among Discharged COVID-19 Patients in Wuhan, China - Li, Li; Wu, Michael Shengtao; Tao, Junxiu; Wang, Weijun; He, Jing; Liu, Ru; Guo, Juan; Chen, Yun; Li, Kejian; Li, Shilong; Qi, Bo; Han, Buxin (Frontiers in Public Health, 2021)
Objective: To understand the mental health status and its risk factors among discharged COVID-19 patients during the first month of centralized quarantine and the subsequent home isolation. Methods: The scales of the Insomnia Severity Index (ISI), General Anxiety Disorder (GAD-7), and Patient Health Questionnaire (PHQ-9) were used to measure the symptoms of insomnia, anxiety, and depression in 782 COVID-19 patients during the first month of centralized quarantine (March 16 to 26, 2020) and then during home isolation (April 3 to 10, 2020). Results: During the centralized quarantine, the prevalence rates of insomnia, anxiety, and depressive symptoms were 44.37, 31.59, and 27.62%, respectively, and those during the home isolation decreased significantly at 27.11, 17.26, and 16.11%, respectively. In both waves, women showed a higher prevalence of symptoms of poor mental health compared to men, and middle-aged (40–59 years old) and elderly (≥60 years old) showed a higher risk of symptoms of poor mental health compared to the younger. In addition, the severity of COVID-19 revealed no significant relationship to symptoms of poor mental health, whereas, the interaction analysis revealed that those with other underlying diseases showed more symptoms of poor mental health during the centralized quarantine and a greater decrease during the follow-up home isolation. Conclusion: The discharged COVID-19 patients suffered from mental health problems such as, insomnia, depression, and anxiety, and this was especially so for women, the middle-aged and elderly, and those with underlying diseases, but along with the rehabilitation and the environmental change from centralized quarantine to home isolation, all the mental symptoms were significantly alleviated. Based on a follow-up investigation, the current results provide critical evidence for mental health and early rehabilitation upon the discharged COVID-19 patients.